Step by step solution :<span>Step 1 :</span><span>Equation at the end of step 1 :</span><span><span> (((3•(x2))•(y4))3)
4•——————————————————
((2x3•(y5))4)
</span><span> Step 2 :</span></span><span>Equation at the end of step 2 :</span><span><span> ((3x2 • (y4))3)
4 • ———————————————
24x12y20
</span><span> Step 3 :</span><span> 33x6y12
Simplify ————————
24x12y20
</span></span>Dividing exponential expressions :
<span> 3.1 </span> <span> x6</span> divided by <span>x12 = x(6 - 12) = x(-6) = 1/<span>x6</span></span>
Dividing exponential expressions :
<span> 3.2 </span> <span> y12</span> divided by <span>y20 = y(12 - 20) = y(-8) = 1/<span>y8</span></span>
<span>Equation at the end of step 3 :</span><span> 27
4 • ——————
16x6y8
</span><span>Step 4 :</span>Final result :<span> 27
—————
4x6y<span>8</span></span>
Answer:
x=17
Step-by-step explanation:
53+(2x+3)=90
Step-by-step explanation:
Solve the system via elimination (add the equations):
-10y + 9x = -9
+ (10y + 5x = -5)
-----------------------
14x = -14
x = -1
Plug in the value for 'x' into the second equation:
-10y + 5(-1) = -5
Solve for y:
-10y - 5 = -5
--> -10y = 0
--> y = 0
x = -1
y = 0